The Use of Context Clues on Reading Comprehension - Widyaningrum, Lulut (ENCOUNTER, 2012)
The ability to understand the English text is greatly importance for the language learners. They have to master it to get knowledge or information. However, it is sometimes difficult for the language learners to convey the difficult or unfamiliar words in their reading. Mostly, it is because of lack of vocabulary of the target language. Then, context clues are supposed to be able to help the learners to increase their reading ability.